Hermeneutika Liberatif Farid Esack: Signifikansi Pemikirannya di Indonesia - Muhammad Hasani Mubarok; Sulaiman; Abdullah Gufronul Mustaan (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
This study describes Farid Esack's thought in Al-Quran Hermeneutics. Farid Esack is an initiator of liberative praxis Hermeneutics who always tries to position the Qur'an in a pattern of partiality that is concrete and nuanced in praxis. So that the Qur'an is used as a guide in human life, but there are many thinkers from both the West and the East. A thinker or scientist from Islam, namely Farid Esack, Farid Esack is an Islamic scholar of black African descent, who discusses the Hermeneutics of the Qur'an. In this study hermeneutics as a tool to understand the Qur'an in various aspects. This research is included in the literature review cluster, which takes data from various literatures and references that make the centre of the study focus on Farid Esack's thoughts. Farid Esack explained about African pluralism and how to position the Qur'an in life. Farid Esack offers an idea in understanding the Hermeneutics of the Qur'an with the keys to understanding it with the previous initiators. In the Indonesian context, Farid Esack views that injustice when the Qur'an relates the doctrine to it is carried out in a real socio-historical context and believes that sincere belief in the oneness of God and final accountability to Him, describes the figure of infidel, and the Koran denounces kufr as hostile behaviour towards Islam and Muslims, and the Koran is also specific about the kuffar's motives for refusing to hold certain beliefs.